Enhancing Learning Outcomes: A Meta-Analysis of the Effectiveness of STEM Education Approaches - Annisa Tishana; Ganefri Ganefri; Asmar Yulastri; Giatman Giatman; Fuji Astuti; Dedy Irfan; Hansi Effendi (AL-ISHLAH: Jurnal Pendidikan, 2025)
This study investigates the effectiveness and variability of STEM education implementation in Indonesian vocational (SMK) and senior secondary (SMA) schools. Given the growing emphasis on STEM to enhance critical 21st-century skills, understanding the consistency and influencing factors of its outcomes is essential. A meta-analysis was conducted, incorporating multiple studies on STEM education implementation. The analysis focused on effect size, heterogeneity, and the factors contributing to outcome variability. Data visualization techniques and statistical models were employed to assess consistency across studies. The analysis revealed a high degree of heterogeneity among the studies (I² = 82.604%), indicating substantial differences in research design, methods, and participant characteristics. Despite this variability, the combined effect size was significant (intercept estimate = 0.307, p 0.001), with a 95% confidence interval of 0.128–0.485. This confirms that the STEM approach consistently yields positive outcomes, particularly in fostering critical thinking, creativity, and collaboration. The findings suggest that despite contextual differences, STEM education provides meaningful benefits. However, variations in implementation—driven by factors such as teaching quality, resources, and institutional support—impact effectiveness. To reduce this disparity, policy integration is needed to support teacher training, industry collaboration, and resource allocation. A holistic, well-supported, and context-sensitive approach to STEM education is essential. Strengthening teacher competency, ensuring adequate facilities, and aligning with industry needs can enhance the effectiveness and sustainability of STEM initiatives in secondary education.